Wiidhaa : an introduction to Gamilaraay - Giacon, John (ANU Press, 2020)
The Gamilaraay language declined in use for many years after the colonisation of Australia. From around 1990, Gamilaraay people and others have been working to revive the language. This book draws on recent research into previous records and analyses of Gamilaraay and of the closely related, and better recorded, Yuwaalaraay. It provides an introduction to many aspects of the language including verbs, the case system and the extensive pronoun paradigm, in a format that students have found very helpful for the last 12 years.?